Agronomic performance and selection of sweet-potato genotypes grown from seeds - Rós, Amarílis Beraldo; Narita, Nobuyoshi; Cardoso, Antônio Ismael Inácio; Hirata, Andréia Cristina Silva (Comunicata Scientiae, 2023)
The low availability of varieties adapted to different crop regions, mainly regarding edaphoclimatic conditions, is one of the causes of low sweet-potato crop yields. The objective of this work was to evaluate agronomic characteristics of sweet-potato plants, from the crossing between the genotypes Londrina and Uruguaiana, grown in the region of Presidente Prudente, SP, Brazil, to select materials with high commercial yield and desirable tuberous root shape and color. The natural crossing between the genotypes Londrina and Uruguaiana grown in alternating rows resulted in 2,430 potentially viable seeds. These seeds were used for growing seedlings whose vines were grown in the field for selecting genotypes with desirable characteristics. The results showed a high diversity in skin and flesh colors; number of tuberous roots per plant, shape, fresh and dry weights, and total and commercial yields of tuberous roots. The selected genotypes were then evaluated in three experiments. Several genotypes presented higher commercial yield than their parents. Three genotypes were approved as cultivars by presenting superior agronomic characteristics than their parents.